HAYBRID MARKETING: KOMBINASI PEMASARAN DIGITAL DAN OFFLINE DALAM MENINGKATKAN DAYA SAING DI UUS HIJAB - Ainol Yaqin, Moh.; Sholehah, Selviatus (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Competition in the Muslim fashion industry, particularly in the hijab sector, has become increasingly intense due to the rapid development of technology and changes in consumer behavior. Ultra Micro Enterprises (UMEs) in this sector need to adopt effective marketing strategies to remain competitive and grow. Hybrid marketing, which combines digital marketing and offline marketing, has become a relevant approach to enhancing the competitiveness of UUS Hijab brands. Digital marketing through social media, marketplaces, and websites allows for broader reach and direct interaction with customers. Meanwhile, offline marketing, such as bazaar events, community engagement, and word-of-mouth, still plays an important role in building trust and customer loyalty. This study aims to analyze the effectiveness of hybrid marketing in improving the competitiveness of UUS Hijab brands. Using a case study approach and qualitative methods, the results show that the combination of digital and offline marketing can increase brand awareness, expand market reach, and strengthen customer relationships. Hybrid marketing strategies also provide flexibility in adapting marketing approaches based on consumer preferences. Therefore, UUS Hijab brands are advised to optimize the synergy between digital and offline marketing to enhance their competitiveness and business sustainability.